THE INFLUENCE OF LEADERSHIP, CAREER DEVELOPMENT WORK DICIPLINE, WORK ENVIRONMENT WITH JOB SATISFACTION AS INTERVENING VARIABLE ON THE WORK MOTIVATION OF WORKING MOTIVATIONS OF KARIMUN REGIONAL GOVERNMENT BUGET TEAM EMPLOYEES - Sawaludin, Sawaludin; Indrayani, Indrayani; Khaddafi, Muammar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
The purpose of this study was to determine and analyze the effect of leadership, career developer, work discipline, work environment in job satisfaction with intervening work motivation variables at financial management service. the method used is a questionnaire and distributed to 138 respondents’ analysis of statistical data using SEMPLS (structural equation modeling partial least square) and using path analysis to examine the pattern of the relationship between the influence ig the dependent variable on the independent, both direct and indirect effects with SMART PLS 3.0 software. the results in the study indicate that leadership has a positive and significant effect on organizational commitment with a p-value of 0.000<0.05, communication has a positive significant effect on organizational commitment with a p-value of 0.000<0.05,